ANALYSING THE IMPACT OF INDIA AND US INFLATION ANNOUNCEMENTS ON INDIAN BOND MARKET BEHAVIOUR - Affifaa Mouhamad; Chandrakala D P (IJRDO - Journal of Business Management, 2025)
This study explores how inflation announcements from India and the United States affect the Indian government bond market, specifically focusing on ten-year G-sec yields. Inflation plays a crucial role in shaping expectations about monetary policy, investor behavior, and interest rates. While previous studies have looked at how domestic economic factors influence bond yields, less attention has been paid to the effect of scheduled inflation announcements in India. At the same time, growing global market integration raises questions about how U.S. inflation shocks spill over into the Indian bond market. Using monthly data from April 2014 to March 2025, we analyze the Indian and U.S. Consumer Price Index, ten-year government bond yields, the USD/INR exchange rate, and Brent crude prices. Fully Modified Ordinary Least Squares (FMOLS) is used to study long-term relationships, while a Vector Error Correction Model (VECM) captures short-term dynamics. The study also employs Granger causality tests, impulse response functions, and forecast error variance decomposition to understand the magnitude, direction, and persistence of these effects. The results show that Indian inflation announcements have a noticeable but short-lived impact on domestic bond yields. In contrast, U.S. inflation news has stronger and more lasting effects, highlighting how global signals influence the Indian market. Overall, the findings emphasize the combined impact of domestic and international inflation on Indian bond market behavior, offering practical insights for policymakers, investors, and risk managers.